Are Outlaw Motorcycle Gangs Organized Crime Groups? An Analysis of the Finks MC. Issue 3 (4th March 2019) - Lauchs, Mark
ABSTRACT: Outlaw Motorcycle Gangs (OMCGs) in Australia are subject to over 30 pieces of legislation restricting the movement and association of members. The justification for these acts is the presumption that the OMCG are criminal organizsations. This presumption has not been proven empirically by government agencies nor tested by academic research partly due to the difficulty in obtaining sufficient information. This paper tests the presumption by analyzing the data contained in the Queensland Police Service's application to the Supreme Court to list the Finks MC, Gold Coast, as a criminal organization.